A User‐Centric Evaluation Procedure for the Design of Child‐Resistant Medicine Bottles. Issue 2 (15th December 2014) - Lin, Ming‐Chyuan; Chen, Ming‐Shi; Lin, Yi‐Hsien; Hung, Yu‐Ching
Abstract Recently, people have begun to realize the importance of child‐resistant (CR) medicine packaging. However, most manufacturers and designers have not been able to effectively provide prevention strategies or design criteria to protect consumers. This research proposes a systematic approach to analyze CR packaging design problems and experiments to evaluate the identified design parameters and to generate the most suitable CR medicine packaging design. The design of a CR packaging bottle is used as an example to help explain the development procedure. During the development procedure, user trials, questionnaires, and children's anthropometric data on bottle opening and hand operations are analyzed. Five design parameters, specifically the cap diameter, cap height, bottle height, bottle diameter, and torsion, are identified and used to perform a Taguchi orthogonal array experimental analysis. A computer‐aided design system is also built to help generate the most suitable design alternatives. The results should assist designers in determining the most important CR design parameters and their most suitable combinations for bottle and related CR medicine packaging design.